Proptosis in Otorhinolaryngology: An Overview - Nazeer, Novshaba; Ivaturi, Phani Bhushan (International Archives of Otorhinolaryngology, 2020)
Introduction Ear, nose and throat (ENT)pathologies can present with proptosis as the early manifestation. The majority of ENT pathologies present with ocular manifestations, due to close anatomical relationship.Objective To study proptosis in ENT disorders in terms of etiology, pathogenesis, and management.Methods The present article is a prospective study conducted at a tertiary care center, in Telangana, India. Patients presenting with proptosis secondary to ENT disorders were thoroughly evaluated and subjected to surgical exploration after providing a signed informed consent.Results Sixty cases of proptosis secondary to ENT disorders have been reported. The most common cause was sinonasal squamous cell carcinoma followed by juvenile nasopharyngeal angiofibroma and allergic fungal rhinosinusitis.Conclusion Many ENT disorders can present with proptosis. Proptosis needs to be evaluated completely for proper management and to limit the morbidity associated with it.
Keywords: proptosis; orbit; Graves'disease; ethmoid